Advances in nanosystems for controlled drug delivery in dentistry: classification and therapeutic applications - Maldonado-Villamizar , Johana (2026)
Nanomedicine has transformed drug delivery through the development of nanosystems capable of releasing therapeutic agents in a controlled manner. This article reviews the classification of nanosystems based on their composition (lipid-based, polymeric, inorganic, and biomolecule derived) focusing on their structure, synthesis process, and dental applications. Compared to conventional therapies, nanosystems offer advantages such as enhanced tissue penetration, optimized pharmacokinetics, and reduced toxicity. A literature review was conducted using scientific publications from 2010 to June 2025, including original studies and systematic reviews retrieved from PubMed, Cochrane Library, and Scopus. The findings demonstrate that nanosystems present a promising alternative for improving bioavailability and enabling precise therapeutic targeting across various tissues, with significant potential for oral cavity applications. In conclusion, while nanosystems represent a promising platform to advance the efficacy and safety of clinical treatments, challenges related to scalability and long-term toxicity remain. These issues represent critical barriers that must be addressed to enable their integration into real-world clinical settings.